Ontology of Offers - Jan Andreasik (Barometr Regionalny)
In the paper, the ontology of individual object and interpretation of it in the area of offers of goods and services is presented and reconstructed by the author. The ontology is defined on the basis of Roman Ingarden’s formal ontology, in particular on the basis of the theory of individual object.